2021
DOI: 10.1186/s12864-020-07288-1
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of genome-wide association studies for average daily gain and lean meat percentage in two Duroc pig populations

Abstract: Background Average daily gain (ADG) and lean meat percentage (LMP) are the main production performance indicators of pigs. Nevertheless, the genetic architecture of ADG and LMP is still elusive. Here, we conducted genome-wide association studies (GWAS) and meta-analysis for ADG and LMP in 3770 American and 2090 Canadian Duroc pigs. Results In the American Duroc pigs, one novel pleiotropic quantitative trait locus (QTL) on Sus scrofa chromosome 1 (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 45 publications
0
28
2
Order By: Relevance
“…Further demonstrated that the uniformities of these three conformation traits in AOD pigs were higher than that of COD pigs. Interestingly, our previous study showed that compared to the COD population, the coefficient of variation for the lean meat percentage (LMP) and average daily gain (ADG) was smaller in the AOD population ( 25 ). In addition, compared to the COD population, the mean of LMP and ADG were higher in the AOD population.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Further demonstrated that the uniformities of these three conformation traits in AOD pigs were higher than that of COD pigs. Interestingly, our previous study showed that compared to the COD population, the coefficient of variation for the lean meat percentage (LMP) and average daily gain (ADG) was smaller in the AOD population ( 25 ). In addition, compared to the COD population, the mean of LMP and ADG were higher in the AOD population.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, PCA was conducted for experimental populations before GWAS analysis to detect the potential population stratification. The PCA plot was presented in our previous paper ( 25 ). The PCA plot showed that AOD and COD pigs were classified clearly into two clusters, indicating that these two populations have different genetic backgrounds.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we identified ROHet in two Duroc populations and found that the distribution of ROHet island and the were different in two Duroc populations. According to our previous study ( Zhou et al, 2021 ), the genetic background of the two Duroc populations are different due to the different intensity and direction of selection, which may lead to diverse heterozygosity-rich regions in the genome. Additionally, Williams et al (2016) found that heterozygosity-rich regions were not randomly distributed in the Chillingham cattle genome, but rather than clustered in specific chromosomal regions, in analogy to ROH and defined as ROHet.…”
Section: Discussionmentioning
confidence: 99%
“…When the population is stratified, the conventional method is to use a fixed effect covariate matrix ( Q matrix) or PCA to control the false positive caused by population structure. Meta-analysis can increase power, reduce false-positive findings, and even identify new genetic loci, so it can solve the shortcomings of single-population GWAS [ 28 ]. In this study, we tried to perform independent GWAS by subgroups and then perform meta-analysis on the significant SNPs obtained by independent analysis.…”
Section: Discussionmentioning
confidence: 99%